Advances on liver cell‐derived exosomes in liver diseases. Issue 1 (27th November 2020) - Jiao, Yan; Xu, Ping; Shi, Honglin; Chen, Dexi; Shi, Hongbo
Abstract: Exosomes are extracellular vesicles with diameters ranging from 30 to 150 nm, which contain several donor cell‐associated proteins as well as mRNA, miRNA, and lipids and coordinate multiple physiological and pathological functions through horizontal communication between cells. Almost all types of liver cells, such as hepatocytes and Kupffer cells, are exosome‐releasing and/or exosome‐targeted cells. Exosomes secreted by liver cells play an important role in regulating general physiological functions and also participate in the onset and development of liver diseases, including liver cancer, liver injury, liver fibrosis and viral hepatitis. Liver cell‐derived exosomes carry liver cell‐specific proteins and miRNAs, which can be used as diagnostic biomarkers and treatment targets of liver disease. This review discusses the functions of exosomes derived from different liver cells and provides novel insights based on the latest developments regarding the roles of exosomes in the diagnosis and treatment of liver diseases.